A tale of a tail: a tidally disrupting ultra-diffuse galaxy in the M81 group. Issue 2 (2nd November 2022) - Žemaitis, Rokas; Ferguson, Annette M N; Okamoto, Sakurako; Cuillandre, Jean-Charles; Stone, Connor J; Arimoto, Nobuo; Irwin, Mike J
ABSTRACT: We present the discovery of a giant tidal tail of stars associated with F8D1, the closest known example of an ultra-diffuse galaxy (UDG). F8D1 sits in a region of the sky heavily contaminated by Galactic cirrus and has been poorly studied since its discovery two decades ago. The tidal feature was revealed in a deep map of resolved red giant branch stars constructed using data from our Subaru Hyper Suprime-Cam survey of the M81 Group. It has an average surface brightness of μ g ∼ 32 mag arcsec −2 and can be traced for over a degree on the sky (60 kpc at the distance of F8D1) with our current imagery. We revisit the main body properties of F8D1 using deep multiband imagery acquired with MegaCam on CFHT and measure effective radii of 1.7–1.9 kpc, central surface brightnesses of 24.7–25.7 mag, and a stellar mass of ∼7 × 10 7 M ⊙ . Assuming a symmetric feature on the other side of the galaxy, we calculate that 30–36 per cent of F8D1's present-day luminosity is contained in the tail. We argue that the most likely origin of F8D1's disruption is a recent close passage to M81, which would have stripped its gas and quenched its star formation. As the only UDG that has so far been studied to such faint surface brightness depths, the unveiling of F8D1's tidal disruption is important. It leaves open the possibility that many other UDGs could be the result of similar processes, with the most telling signatures of this lurking below current detection limits.